GOLD SAVINGS MONITORING APPLICATION AT PT PEGADAIAN - Ryan Andrian, Mohamad; Lamria Siregar, Suzanna (Dinasti International Journal of Management Science, 2022)
In this global era, digital plays a very important role in life now and in the life to come. Because everyone needs digitization, pawn companies are here to provide their best services for the people in Indonesia. Their best services are making it easy to invest and being able to manage money well, Digitalization is very important in today's global era because everyone needs investment from small children to the elderly, with a pawn company that can make it easier for them to carry out activities such as pawning, purchases of precious metals and gold savings. Design and implementation of applications for monitoring gold savings transactions at PT. Pegadaian. The use of applications that underlie this research include Grafana Applications and Agile Methods. Grafana application as an open source sensor monitoring, visualization and analytical system. This method is for software development. Which consists of Requirements, Design, Develop, Test and Deploy.